Explor Neuroprot Ther 2023
DOI: 10.37349/ent.2023.00056
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of transcutaneous vagus nerve stimulation as a treatment option for adjuvant cancer and heart failure therapy

Niklas Frank,
Michiaki Nagai,
Carola Y. Förster

Abstract: Vagus nerve stimulation (VNS) has gained prominence in the treatment of various clinical disorders such as migraine, depression, and tinnitus. Based on increased scientific knowledge of the VNS and insights into the vagus nerve (VN) function and anatomy/conduction, robust treatment approaches have been developed. There are both noninvasive and invasive VNS (iVNS) techniques. Currently, only iVNS techniques are approved by the US Food and Drug Administration (FDA). In contrast, transcutaneous VNS (tVNS) is a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 222 publications
0
4
0
Order By: Relevance
“…At this point, tVNS treatment can be very effective. Frank et al [14] showed that tVNS has a positive effect on parasympathetic activity and plays an important role in reducing chronic pro-inflammatory markers. However, as far as its applicability is concerned, clinical studies and results are still lacking and should be the subject of future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point, tVNS treatment can be very effective. Frank et al [14] showed that tVNS has a positive effect on parasympathetic activity and plays an important role in reducing chronic pro-inflammatory markers. However, as far as its applicability is concerned, clinical studies and results are still lacking and should be the subject of future research.…”
Section: Discussionmentioning
confidence: 99%
“…As we have shown in our recent research, there is a strong correlation between chronic inflammation and hyperactivity of the SNS. Anti-inflammatory results have been observed when stimulating the parasympathetic nervous system [14], suggesting that the stimulation of the VN may also have beneficial effects on the prevention of TTS, a stress-induced cardiomyopathy.…”
Section: Inflammagingmentioning
confidence: 99%
See 1 more Smart Citation
“…For an extensive discussion of the topic and of all clinical studies performed so far, the interested reader is referred elsewhere [106,107]. Finally, noninvasive, transcutaneous VNS, delivered at the tragus of the ear, where the auricular branch of the vagus nerve is located, has also been under active investigation in recent years, with promising results [187,188].…”
Section: Icns Modulation In Heart Failurementioning
confidence: 99%